Stupidity in the Age of Reason (Global Journal of Human-Social Science, 2019)
The Age of Reason was marked by a decline in the theological basis of knowledge due to a rise of scientific explanations of natural phenomena trends which reflected the application of reason to philosophy astronomy where it was most effective and biology However during this era the political life of nations continued to be shaped by power while the cognitive life of people continued to be shaped by religion tradition and emotion which combined to make this period as unreasonable as any other